GURU SEJARAH SEBAGAI AGEN PERUBAHAN DALAM PENGGUNAAN MEDIA PEMBELAJARAN INOVATIF ABAD 21 - Ansar, Mutakharah; Bahri, Bahri (Humano: Jurnal Penelitian, 2024)
This research aims to identify challenges and innovations in teaching history in the 21st century and explore the role of teacher professionalism in improving the quality of education. The method used is literature study, namely reviewing data that already exists and is ready to be used. The research results show that history teachers need to have high professionalism, technological skills, and the ability to create innovative learning in order to compete at the global level. Innovations in learning, such as the use of creative media and information technology, are critical to increasing student engagement and understanding. Key challenges include the need to overcome student boredom, utilize technology effectively, and ensure that history learning is relevant and contextual. It was found that creative and innovative history teachers can create a dynamic and interesting learning environment that helps students understand the material better and develop good character. This research emphasizes the importance of infrastructure support and training for teachers to integrate technology in history learning effectively. Thus, history teachers in the 21st century are expected to be able to overcome the challenges of globalization and take advantage of existing opportunities to improve the quality of education and produce competent and highly competitive human resources.